A pessoa com Transtorno do Espectro do Autismo: a inclusão e o direito à educação - Massud, Sandra Lucia Garcia (2019)
This work contextualizes the Autism Spectrum Disorder in the panorama of the rights of the person with intellectual disability in its several aspects. From this perspective, it demonstrates the recognition of disabled people by international and domestic normative sources, with emphasis on the right to education, considering its roots and its importance in the individual development process. The study begins by presenting the conception of the person with intellectual disability in world history, from contempt to compassion, in the face of the evolution of knowledge. Then, in the Brazilian history, the research focuses on the first health and education treatments available to people with intellectual and mental disorders until the twentieth century. Basing the theme on international standards, especially the international human rights treaties of which Brazil is part, with special attention to the International Convention on the Rights of Persons with Disabilities, its guidelines and principles. This way, the subject is examined from the point of view of the concepts and principles of the 1988 Federal Constitution and the Statute of the Disabled. Continuing, we analyze the history, signs and characteristics of Autism Spectrum Disorder, based on literature in the areas of psychiatry, neurology and psychology, as well as highlighting Law No. 12.764/2012, and its implications for the development and implementation of inclusive education of the person with Autism Spectrum Disorder. Finally, discussing inclusive education in Brazil, centered on recent legislation and considerations on student learning with Autism Spectrum Disorder, is complementing by critiques and notes for the best materialization of rights under consideration